8-methoxypsoralen Potentiates Solar UV-Induced DNA Damage of Skin Melanocytes. (14th June 2022) - Hoang, Megan; Cho, Eunyoung; Oancea, Elena
Abstract: Objectives: There is little research on how diet may influence skin cancer. 8-methoxypsoralen (8-MOP) is a photocarcinogenic dietary furocoumarin that exists in parsley, parsnip, and celery. Phototherapy that uses 8-MOP and ultraviolet radiation (UVR) exposure to treat skin disorders is known to induce skin cancer. However, the biological mechanism of its carcinogenicity is not understood. We aimed to determine whether 8-MOP affects the extent of UVA-induced DNA damage in human epidermal melanocytes, the origin of melanoma, the most fatal type of skin cancer. Methods: Oxidative DNA damage leads to the phosphorylation of H2AX (a member of the histone H2A family), generating γ-H2AX. We used γ-H2AX as a marker for DNA damage in human epidermal melanocytes untreated or treated with 100 μM 8-MOP for 12 hours and exposed or not to 3J/cm2 UVA. Each of the 4 groups were analyzed by western blots using H2AX and γ-H2AX antibodies. We used ImageJ/FIJI software for densitometric analysis to quantify the band intensities. The intensities of γ-H2AX bands were divided by that of H2AX bands (γ-H2AX/total H2AX) to measure the amount of DNA damage. To measure how 8-MOP interacts with UV to affect DNA damage, the UV: Control ratios for untreated and 8-MOP treated cells were calculated as the ratio of γ-H2AX/total H2AX in cells exposed to UV to that of cells without UV. T-tests were performed to calculate the significances of differences between γ-H2AX/total H2AX and between UV: Control ratios of the 4 groups. Results: The mean UV: Control ratio for 8-MOP treated cells was borderline significantly higher than the mean UV: Control ratio for untreated cells ( p  = 0.07), suggesting that 8-MOP interacts with UV to enhance DNA damage. When cells were treated with 8-MOP and exposed to UV, γ-H2AX/total H2AX increased compared to untreated cells exposed to UV, although the increase was not statistically significant ( p  = 0.20). Conclusions: 8-MOP potentiates UVA-induced DNA damage in melanocytes, which could be one of the mechanisms how 8-MOP and UV exposure induce skin cancer. Other dietary furocoumarins in fruits and vegetables should be evaluated in terms of the effect on DNA damage. Funding Sources: Brown Cancer Center.